2012
DOI: 10.4103/0019-5278.99684
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hearing loss of the workmen of an open cast chromite mines

Abstract: Background:The present work aimed at to describe hearing threshold based on audiometry data of the mine workers based on their age, work station and years of working of an open cast chromite mine in Odisha, India at high fence.Materials and Methods:A cross-sectional study of hearing threshold of the subjects of the chromite mine was carried out. Audiometric data of 500 subjects were taken from the hospital of the mines of Sukinda Valley, Jajpur, Odisha, India. The latest audiometry data available during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The null hypothesis assumed that there is no significant difference between left and right ears with respect to hearing level. A two-tailed t-test was conducted and found that there was indeed no significant difference between left and right ears (p > 0.05), associated with the study of Kerketta et al [15], which studied the hearing loss among workmen at open-cast chromite mines. The t-test also reveals no significant difference in hearing loss between both ears due to age, work experience, noise exposure level and work characteristic at all test frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…The null hypothesis assumed that there is no significant difference between left and right ears with respect to hearing level. A two-tailed t-test was conducted and found that there was indeed no significant difference between left and right ears (p > 0.05), associated with the study of Kerketta et al [15], which studied the hearing loss among workmen at open-cast chromite mines. The t-test also reveals no significant difference in hearing loss between both ears due to age, work experience, noise exposure level and work characteristic at all test frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…These reviews included the above electronic database online literature searches related to NIHL in animal models and human [Tables 1 and 2 ]. [ 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] The information regarding numbers of publication on NIHL from Asian countries was obtained from ISI Web of Science [ Figure 5 ]. According to the database, only five publications on NIHL were reported from India.…”
Section: S Ource Of D Atamentioning
confidence: 99%